Dealing with High Debt in an Era of Low Growth - Abbas, S. M. Ali (Staff Discussion Notes; Staff Discussion Notes ;, 2013)
task has become particularly challenging in European advanced economies where expectations of low growth and limits to monetary policy support are shifting the burden of adjustment onto fiscal consolidation. The SDN will investigate the main drivers behind successful past debt reversals, focusing on macroeconomic and financial market conditions, the speed and form of fiscal adjustment, and the institutional policy setting, among other things. Its policy conclusions will depend on the emerging stylized facts but are likely to include considerations on the design and pace of fiscal consolidation, taking into account country-specific as well as regional economic, institutional, and political factors.